Mediating Role of Self-Concept in Moral Development and Risk-taking Behaviours among Children - Misbah Waqar, Saleha Bibi (JECCE, 2023)
Present study was done to investigate the mediating role of self-concept in moral development and risk-taking behavior among children. Aim of the study was to explore the role of self-concept as a mediator between moral development and risk-taking behavior among children. Study was done on the sample size of 300 children. Sample of the study was selected though purposive-convenient sampling technique. Sample was selected from the government and private schools of Rawalpindi. Moral development was measured through Bandura scale for moral disengagement. Self-concept of the children was measured using Braken scale for self-concept and risk -behaviors among children were measured through sensation seeking scale by zakerman. It was hypothesized that self-concept act as mediator between moral development and risk-taking behaviors among children. Data was statistically analyzed through using SPSS. Result of our study showed that self-concept is a strong mediator of moral development and risk-taking behavior among children. Furthermore, our study revealed that self-concept is a strong predictor of moral justification, distortion of possible consequences, diffusion of responsibility, dehumanization and attribution of blame. Our study also revealed that girls scored significantly high on moral justification, distortion of possible consequences and diffusion of responsibility whereas boys scored significantly high on the risk-taking behaviors. Our findings have strong implications for child psychopathology.